Answer:
The nth term of the given sequence
![a_{n} = a_{n-1} + (2n-1)](https://tex.z-dn.net/?f=a_%7Bn%7D%20%3D%20a_%7Bn-1%7D%20%2B%20%282n-1%29)
Step-by-step explanation:
<u><em>Explanation:-</em></u>
Given sequence -5,-4,-1,4,11,20,31
a₀ = -5
a₁ = a₀ +1 = -5 +1 = -4
a₂ = a₁ + 3 = -4+3 = -1
a₃ = a₂ + 5 = -1 +5 = 4
a₄ = a₃ + 7 = 4 + 7 =11
a₅ = a₄ + 9 = 11+9 = 20
a₆ = a₅ + 11 = 20+11 = 31
a₇ = a₆ + 13 = 31 +13 =44
and so on
The nth term of the given sequence
![a_{n} = a_{n-1} + (2n-1)](https://tex.z-dn.net/?f=a_%7Bn%7D%20%3D%20a_%7Bn-1%7D%20%2B%20%282n-1%29)
The answer for the first question would be 3952+3952 =7903
Answer:
6^8
Step-by-step explanation:
6^4 * 6^4
We know that a^b * a^c = a^(b+c)
6^4 * 6^4 = 6^(4+4) = 6^8
Answer:
The answer would be 9
Step-by-step explanation: